The optimization design of hospital bed structure for independently separating left and or right leg using genetic algorithms - Atthaphon Ariyarit (2018)
This paper deals with the new method to design the optimum design for hospital bed, which can separate the left and or right leg for patient's leg splint. GAs as an optimization method was selected to search the minimum mass of bed structure whilst fulfilling some structure constraints such as stress, displacement and buckling. The GAs and FE code were developed to analyze the structure in MATLAB. This paper showed the success in searching the minimum mass whilst the stress and displacement were accepted. The optimum design for the hospital bed was 49.25 kg. © (2012) Trans Tech Publications, Switzerland.